A novel multi-timescale comprehensive drought index for drought monitoring in the Xijiang River Basin - Liping Wang; Shufang Wang; Jing Li; Xingnan Zhang (Journal of Hydrology: Regional Studies)
Study region: Xijiang River Basin, China. Study focus: Drought indices are vital tools for monitoring drought events; however, existing indices often fail to simultaneously characterize both traditional and flash droughts. In this study, a novel multi-timescale comprehensive drought index, named the Standardized Precipitation Potential Evapotranspiration Soil Moisture Index (SPPSI), was developed by integrating precipitation, potential evapotranspiration, and soil moisture, three key drought-driving factors. The SPPSI was constructed by fitting optimal marginal distributions for each factor, employing a D-vine copula structure, and selecting an optimal pair-copula function. New hydrological insights for the region: The SPPSI effectively captures the nonlinear and asymmetric relationships among precipitation, potential evapotranspiration, and soil moisture. Compared to the Standardized Precipitation Evapotranspiration Index (SPEI) and Standardized Soil Moisture Index (SSMI). The SPPSI demonstrates improved capability in identifying critical drought characteristics, such as onset, duration, and termination, and offers a more accurate representation of real drought conditions during typical drought events. It also shows a stronger correlation with drought-affected areas. Notably, the SPPSI at a 5-day timescale is capable of effectively detecting the development of flash droughts. The SPPSI is capable of monitoring both flash and traditional droughts. It supports flexible drought analysis across multiple timescales (5-day, 1-month, 3-month, 6-month, 12-month, and 24-month) based on specific research needs. This study provides theoretical support for improving drought monitoring across multiple drought types.